2014
DOI: 10.1016/j.mjafi.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Statins: Can we advocate them for primary prevention of heart disease?

Abstract: a b s t r a c tThe discovery of cholesterol-lowering agents, namely HMG-CoA reductase inhibitors or statins, ushered in a series of large cholesterol reduction trials. The first of these studies was the Scandinavian Simvastatin Survival Study (4S) in which hypercholesterolemic men with CHD who were treated with simvastatin had a reduction in major coronary events of 44% and a reduction in total mortality of 30%. Many more secondary prevention trials followed to establish unequivocally the benefit of cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Ato is a lipid-regulating statin that functions by inhibiting the synthesis of 3-hydroxy-3-methyl glutaryl coenzyme A reductase (30). However, its non-lipid-regulating roles have not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ato is a lipid-regulating statin that functions by inhibiting the synthesis of 3-hydroxy-3-methyl glutaryl coenzyme A reductase (30). However, its non-lipid-regulating roles have not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are able to block 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase, which reduces the cholesterol synthesis (30) and blocks the production of isoprenylated products in the mevalonate pathway (38). As RhoA protein can therefore not be prenylated, a large number of inactive RhoA protein accumulate in the cytoplasm, extending the half-life of eNOS mRNA (38).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, alternative approaches are eagerly needed; plant-based therapies attract much interest as they are effective in reducing lipid levels [3]. The treatment for hypercholesterolemia and CVDs with medicinal plants has increased and seems to produce lower undesirable side effects [4]. Several reports have shown that herbal medicine reduces lipid peroxidation in blood, has anti-cancer activity in vitro and it is useful for treating infectious disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of isoprenoid compounds (the so-called "multiple action" effect of statins) results in a loss of protein isoprene and reduction of coenzyme Q-10, which promotes apoptosis, oxidation and permanent mitochondrial localization defect (Mammen and Amato, 2010). Uncommon adverse events include arthropathy, liver toxicity, insomnia, memory loss, insanity, peripheral neuropathy, erectile dysfunction, diabetes, impaired myocardial contractility, and autoimmune diseases (Godlee, 2014;Ray et al, 2014). Therefore, the method of local administration chosen in this study is to reduce the adverse effects of simvastatin on the system.…”
Section: Discussionmentioning
confidence: 99%